Endoscopic Surgery in Children - Bax, N. M. A.; Georgeson, Keith E.; Najmaldin, Azad S.; Valla, Jean-Stéphane (Springer Berlin Heidelberg, 1999)
Endoscopic surgery in children is a rapidly expanding field in pediatric surgery. This book represents the state of the art, and explains why endoscopic surgery in children is so important. General aspects are discussed and detailed information is provided on many specific operations both in the chest as well as in the abdomen, including endoscopic treatment of throracic scoliosis, of urogenital conditions, and of neurosurgical conditions. Application of endoscopic techniques in oncology is discussed as well. A special chapter deals with complications